2008
DOI: 10.1002/jbm.a.31969
|View full text |Cite
|
Sign up to set email alerts
|

Controlled delivery of paclitaxel from stent coatings using novel styrene maleic anhydride copolymer formulations

Abstract: The controlled release of paclitaxel (PTx) from stent coatings comprising an elastomeric polymer blended with a styrene maleic anhydride (SMA) copolymer is described. The coated stents were characterized for morphology by scanning electron microscopy (SEM) and atomic force microscopy (AFM), and for drug release using high-performance liquid chromatography (HPLC). Differential scanning calorimetry (DSC) was used to measure the extent of interaction between the PTx and polymers in the formulation. Coronary stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…SIBS blends with other polymers have been studied for different applications. For example, SIBS blended with the styrene maleic anhydride (SMA) copolymer was studied for drug-eluting stent coatings . Morphological studies showed that SMA formed a separate phase due to immiscibility with SIBS.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIBS blends with other polymers have been studied for different applications. For example, SIBS blended with the styrene maleic anhydride (SMA) copolymer was studied for drug-eluting stent coatings . Morphological studies showed that SMA formed a separate phase due to immiscibility with SIBS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, SIBS blended with the styrene maleic anhydride (SMA) copolymer was studied for drug-eluting stent coatings. 33 Morphological studies showed that SMA formed a separate phase due to immiscibility with SIBS. In another report, 34 SIBS was blended with poly-(ethylene glycol), and the blends were electrospun into elastic fiber mats for drug release application.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For the diffusion-controlled quasi-stationary process, a mathematically complete set of the exact analytical solutions is obtained in implicit forms for consideration of both dissolution of a particle in a solvent and growth of it by precipitation in a supersaturated environment. Understanding the dissolution behavior of solid particles in liquid plays an important role in pharmaceutical dosage form development (Chen and Wang, 1989;Rice and Do, 2006), and particle growth by precipitation in a supersaturated environment is relevant to the drug-polymer microsphere formation process (Wu, 1995) as well as the observed phase separation process during solvent removal in drying of a coating with the drug-polymer mixture (Barocas et al, 2009;Richard et al, 2009). The commonly used explicit formula based on the solution with quasi-steady-state approximation is shown to provide unsatisfactory accuracy unless the solubility is restricted to very small values (corresponding to < 10 −4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, PoP-coated stents showed severe histiolymphocytic and fibromuscular reactions resembling a foreign body reaction [183]. In another study, the controlled release of Px from the stent coating of an elastomeric polymer mixed with styrene-maleic anhydride (SMA) copolymer demonstrated that Px was compatible with any component of the polymer blend [184]. A native endothelial extracellular matrix mimicking a self-assembled nanofibrous matrix was described as a new treatment model.…”
Section: Improvement Of Drug Delivery Propertiesmentioning
confidence: 99%